THE MANIFESTATION OF FORMING AN INTOLERANT ATTITUDE TOWARD EXTREMISM ON A GLOBAL SCALE (International Congress on Economics, Management and Business Studies, 2026)
This article provides a scientific analysis of the manifestation of forming an intolerant attitude toward extremism on a global scale. It also highlights that at the beginning of the 21st century, the modern security architecture requires protection not only from military and economic threats but also from ideological and ideological risks. One of these threats is the phenomenon of extremism, which has become one of the most urgent issues on the political agenda of the international community.
Keywords: Ideology, society, stability, extremism, radicalism, intolerance, discourse, youth, security, politics, spirituality, education, prevention.